Dietary fibre effects and the interplay with exogenous carbohydrases in poultry nutrition - Bedford, Michael R.; Svihus, Birger; Cowieson, Aaron J. (Animal Nutrition, 2024)
A comprehensive understanding of the role of dietary fibre in non-ruminant animal production is elusive. Equivocal and conflated definitions of fibre coupled with significant analytical complexity, interact with poorly defined host and microbiome relationships. Dietary fibre is known to influence gut development, feed intake and passage rate, nutrient absorption, microbiome taxonomy and function, gut pH, endogenous nutrient loss, environmental sustainability, animal welfare and more. Whilst significant gaps persist in our understanding of fibre in non-ruminant animal production, there is substantial interest in optimizing the fibre fraction of feed to induce high value phenotypes such as improved welfare, live performance and to reduce the environmental footprint of animal production systems. In order to achieve these aspirational goals, it is important to tackle dietary fibre with the same level of scrutiny as is currently done for other critical nutrient classes such as protein, minerals and vitamins. The chemical, mechanical and nutritional role of fibre must be explored at the level of monomeric sugars, oligosaccharides and polysaccharides of varying molecular weight and decoration, and this must be in parallel to standardisation of analytical tools and definitions for speciation. To further complicate subject, exogenous carbohydrases recognise dietary fibre as a focal substrate and have varying capacity to generate lower molecular weight carbohydrates that interact differentially with the host and the enteric microbiome. This short review article will explore the interactive space between dietary fibre and exogenous carbohydrases and will include their nutritional and health effects with emphasis on functional development of the gut, microbiome modulation and host metabolism.